Examining equity in accessibility to multi-tier healthcare services across different income households using estimated travel time - Jin, Tanhua; Cheng, Long; Wang, Kailai; Cao, Jun; Huang, Haosheng; Witlox, Frank (Transport policy, 2022)
Accessibility equity is a critical factor in developing equitable and sustainable communities. Although numerous studies have analyzed accessibility inequity, few of them examined inter-group and intra-group inequity and made comparisons between private cars and public transit. In this paper, a Gaussian-based Two-step Floating Catchment Area method was applied to evaluate the spatial accessibility of multitier healthcare services among different income groups in Shanghai, China. The results show that high-income households have better access to healthcare services than low-income households. The gap between low- and high-income groups increases as the level of healthcare services rises. The Theil index was used to assess inequity between groups and within groups, as well as overall inequity. The inter-group inequity for public transit is greater than that for private cars, suggesting that accessibility by public transit is more unequally distributed across groups of people compared with private cars. Inter-group inequity increases with the tier of healthcare services. The bivariate local Moran index shows that underserved areas are found primarily in low-income neighborhoods. Overall, the research findings indicate the quality of public transit services might have a more significant impact on accessibility inequity than the spatial distribution of health services. This study provides valuable information for designing targeted policy provisions to improve equity and efficiency in healthcare access. •This study examines inter-group and intra-group inequity, as well as total inequity.•Travel time estimation from an online Maps API was applied to assess accessibility.•The gap in accessibility between low- and high-income groups increases as the level of healthcare services rises.•The inter-group inequity in accessibility by public transit is more severe than that by private cars.